New species of Eutarsopolipus (Trombidiformes: Podapolipidae) from the pterostichine genera Castelnaudia and Trichosternus (Coleoptera: Carabidae) in Australia - Seeman, Owen D. (Zootaxa, 2019)
Three new species of Eutarsopolipus Berlese are described from the flightless pterostichine carabid genera Castelnaudia Tschitscherine and Trichosternus Chaudoir found in rainforests in eastern Queensland: Eutarsopolipus piraticus sp. nov. from Trichosternus frater Darlington and T. mutatus Darlington in north-east Queensland; E. uncatus sp. nov. from C. obscuripennis (Macleay) in north-east Queensland; and E. verberatus sp. nov. from Castelnaudia eungella (Darlington) in middle-eastern Queensland and C. wilsoni (Castelnau) in south-east Queensland. These species are unique in Eutarsopolipus by having large hook-like unguinal setae on tarsi II–III. All species differ by only a few minor features, and the geographically isolated populations of E. verberatus could not be distinguished reliably. Surprisingly, the presence/absence of leg I claws and seta v″ on femur I, which have been used to create species groups, is intraspecifically variable. Species delimitation and the tarsal setation of Podapolipidae, particularly Eutarsopolipus, are also discussed.